Viral and Atypical Pathogen’s Epidemiology of a Large Cohort of Patients with Acute Respiratory Tract Infections in Shaanxi Province, Northwest China - Liu X; Li M; Yang T; He R; Guo X; Chen M (International Journal of General Medicine, 2023)
Xinyu Liu,1,* Meng Li,1,* Tian Yang,1 Ruiqing He,1 Xuan Guo,2 Mingwei Chen1 1The Department of Respiratory and Critical Care Medicine of the First Affiliated Hospital of Xi’an Jiaotong University, Xi’an, Shaanxi, People’s Republic of China; 2Laboratory Department of the First Affiliated Hospital of Xi’an Jiaotong University, Xi’an, Shaanxi, People’s Republic of China*These authors contributed equally to this workCorrespondence: Mingwei Chen, The Department of Respiratory and Critical Care Medicine of the First Affiliated Hospital of Xi’an Jiaotong University, 277 West Yanta Road, Xi’an, Shaanxi, People’s Republic of China, Email chenmw36@163.comPurpose: To analyze and summarize the etiological and epidemiological characteristics of acute respiratory tract infections (ARIs) in northwest China to improve the clinical management and prevention of local ARIs.Methods: Patients with ARIs in Shaanxi Province, from January 2014 to December 2018, were retrospectively analyzed. Indirect immunofluorescence assay (IFA) was used to detect the IgM antibody of eight respiratory pathogens.Results: A total of 15,543 eligible patients were included in this study. Overall, 36.01% of the patients (5597/15543) were positive for at least one of eight pathogens, among which single and mixed infections accounted for 74.65% (4178/5597) and 25.35% (1419/5597), respectively. Mycoplasma (MP) showed the highest detection rate (18.12%), followed by influenza virus B (Flu B, 11.65%), chlamydia (CP, 7.00%), respiratory syncytial virus (RSV, 4.18%), parainfluenza virus (PIV, 2.83%), influenza virus A (Flu A, 1.69%), legionella (LP, 1.00%) and adenovirus (ADV, 0.70%). Flu B (17.54%, 759/4327) was the most prevalent virus in patients aged less than 18 years. In addition, common respiratory infections with higher detection rates were found in autumn (39.65%), followed by winter (37.37%), summer (36.21%) and spring (30.91%). There were significant differences in the detection rates of pathogens in different seasons (P < 0.001).Conclusion: These findings serve as a reference for local health authorities to develop further plans for the prevention and control of ARIs.Keywords: acute respiratory tract infections, respiratory viruses, atypical pathogens, epidemiology, etiology